A Study on the Optimization of Grand-Parenting Paths in Rural Areas - HE, NAN (Pacific International Journal, 2023)
In rural areas, young adults in the middle tier often face a difficult choice: seek job opportunities in economically developed areas, or stay behind due to the limited jobs available and the need to secure bilateral parental support and education costs for their children. Unfortunately, the dualistic urban-rural and inter-provincial household registration system restricts children’s opportunities for further education, while the high threshold for public education forces them to complete their education in their hometowns, turning them into left-behind children. Furthermore, the family economy and workforce composition in rural areas often make grand-parenting the optimal choice and an unavoidable reality. However, while grand-parenting may make sense from an economic standpoint, it can have negative consequences on the development of children, including inadequate nutrition, unresponsive care, and a lack of early learning opportunities. To mitigate these negative effects, it is important to optimize the grandparenting model. This can be achieved by adapting it to the child’s needs, improving communication, developing activities, respecting rules, addressing conflicts, and optimizing the grand-parenting pathway. By taking into account both the internal strengths and weaknesses of grand-parenting, as well as external scientific knowledge, we can maximize the positive effects of this caregiving model on children’s development.